Temperature dependence of the piezotronic effect in CdS nanospheres. (June 2021) - Puneetha, Peddathimula; Mallem, Siva Pratap Reddy; Bathalavaram, Poornaprakash; Lee, Jung-Hee; Shim, Jaesool
Abstract: We used simple graphene transfer and microwave synthesis to deposite wurtzite-structured CdS nanospheres with gold nanoparticles (AuNPs) on a flexible polyethylene terephthalate (PET) substrate. The temperature dependence of the piezotronic effect of the CdS nanospheres was studied in the temperature range 240–320 K under tensile strains of 0.00–0.40%, the effect was found to significantly depend on the device temperature. Moreover, the piezotronic effect was enhanced by over 590% at a strain of 0.40% by cooling temperature owing to the improved efficiency of piezoelectric potential charges. This is a result of the decreased screening effect by reduced carrier generation in the CdS. In addition, the consistent charge transfer mechanism in the investigated piezotronic device is explained by the possible energy band diagrams. The results of this analysis provide a comprehensive understanding of the piezotronic effect and provide a direction for future device applications in fields such as health monitoring, human-machine communication, surgical robotics, and artificial intelligence. Graphical Abstract: The temperature dependence of the piezotronic effect CdS nanospheres were studied in different temperatures and with applied strains. The piezotronic effect is enhanced by over 590% by low temperature owing to the improved efficiency of piezoelectric potential charges. This happens due to decreased screening effect by reduced carrier generation in the CdS nanosphere at low temperature. ga1 Highlights: Used simple graphene transfer and microwave synthesis for CdS nanospheres with AuNPs on a flexible PET substrate. Decreased screening effect by reduced carrier generation in the CdS. The piezotronic effect is enhanced by over 590% by low temperature. This piezotronic device provides a direction for future device applications.